2018
DOI: 10.1039/c8ew00232k
|View full text |Cite
|
Sign up to set email alerts
|

Microaeration through a biomembrane for biogas desulfurization: lab-scale and pilot-scale experiences

Abstract: Microaeration through biomembrane; a novel method for biogas desulfurization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This represents that on average about 9% of all the methane produced left the system through the oxygen container. Research carried out by Pokorna-Krayzelova et al [ 23 ] determined methane losses of 3.7% when operating a silicone biomembrane system for sulfide oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents that on average about 9% of all the methane produced left the system through the oxygen container. Research carried out by Pokorna-Krayzelova et al [ 23 ] determined methane losses of 3.7% when operating a silicone biomembrane system for sulfide oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The modification of commercially available membrane modules may be a simple and affordable way to implement a micro-oxygenation module for sulfide oxidation. For example, Pokorna-Krayzelova et al [ 23 ] used a commercially available microfiltration membrane for biogas desulfurization on a pilot scale, with positive results.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to overcome the aforementioned challenges associated with in-situ microaeration desulphurisation strategy, recent investigations have explored the possibility of introducing a membrane to separate the biogas from the oxygen supply pipes [91,92]. In the studies presented in Ref.…”
Section: In-situ Microaeration Desulphurisationmentioning
confidence: 99%
“…[91] and Ref. [92], it was demonstrated that it was possible to utilise an internal silicone membrane and a polyvinylidene fluoride membrane to prevent the clogging problems while maintaining high sulphide removal efficiency of 96% and 99.99%, respectively. These challenges may also be limited by the utilisation of a compartment, distinct from the anaerobic digestion vessel, where the microaeration process for H 2 S oxidation is taking place [93].…”
Section: In-situ Microaeration Desulphurisationmentioning
confidence: 99%
“…In the last few years, many new materials (i.e. silicone, CH 4 -type zeolite and polydimethylsiloxane) for membranes were developed (Maghsoudi & Soltanieh, 2014;Pokorna-Krayzelova et al, 2018a;Tilahun et al, 2018) and their prices decreased rapidly. Recently, a high silica -CH 4 -type zeolite membrane was used for the simultaneous removal of CO 2 and H 2 S (Maghsoudi & Soltanieh, 2014).…”
Section: Membrane Separationmentioning
confidence: 99%